1996
DOI: 10.1128/aem.62.8.2970-2977.1996
|View full text |Cite
|
Sign up to set email alerts
|

Development of metal tolerance in soil bacterial communities exposed to experimentally increased metal levels

Abstract: The development of metal tolerance in soil bacterial communities exposed to different heavy metals was examined under laboratory conditions. An agricultural soil amended with different Zn concentrations was studied most intensively, and measurements were made over a 28-month incubation period by means of the thymidine incorporation technique. Tolerance levels were not affected by metal concentrations lower than 2 mmol of Zn kg (dry weight) of soil ؊1 , but above this value, the level of Zn tolerance increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(99 citation statements)
references
References 42 publications
12
84
0
3
Order By: Relevance
“…By artificially amending a subset of Fe reducers from one site with Cu and comparing it to bacteria sharing an identical exposure history except for the Cu amendment, we were able to isolate the effect of Cu exposure on Cu tolerance. Our results are consistent with findings for aerobic soil bacteria, in which Cu tolerance was enhanced by previous Cu exposure [21]; similar studies with anaerobic bacteria have been performed, but only with methanogens [22]. This is the first report of Cu tolerance in Fe-reducing bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…By artificially amending a subset of Fe reducers from one site with Cu and comparing it to bacteria sharing an identical exposure history except for the Cu amendment, we were able to isolate the effect of Cu exposure on Cu tolerance. Our results are consistent with findings for aerobic soil bacteria, in which Cu tolerance was enhanced by previous Cu exposure [21]; similar studies with anaerobic bacteria have been performed, but only with methanogens [22]. This is the first report of Cu tolerance in Fe-reducing bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…Atlas and colleagues (1991) showed that communities had lower genetic diversity following addition of chemical pollutants, but that the dominant populations within the community possessed enhanced physiological tolerances and substrate utilization capacities. Our results suggest that an adaptive tolerance response may have occurred in survivors (Díaz-Raviña and Bååth, 1996;Bååth et al, 1998), which is consistent with a lack of influence of copper on bacterial diversity.…”
Section: Copper-treated Bacterial Community Diversity Structure and supporting
confidence: 83%
“…Extraction from soil and cultivation of microbial populations can only be done for a very small part of the total soil microbial community [9]. Consequently, the outcome of the laboratory PICT experiments with soil microorganisms is valid only for the corresponding part of the community.…”
Section: Resultsmentioning
confidence: 99%
“…Doelman and colleagues [6,7] and Smit et al [8] have shown increased metal tolerance of terrestrial bacteria isolated from contaminated sites. Díaz-Ravina and Bååth [9] have shown increased metal tolerance of terrestrial bacterial communities to experimentally increased metal levels.…”
Section: Introductionmentioning
confidence: 99%